A novel dual sensitive polymer-gambogic acid conjugate: synthesis, characterization, and in vitro evaluation. (26th September 2019) - Song, Ke; Wang, Zhaobo; Liu, Xue; Zhang, Guolin; Wang, Xin; Ouyang, DeFang; Guo, Mingrui; Chen, Lijiang
Abstract: Currently, bio-simulate drug delivery systems are highly considered for efficient targeting of tumors. Nevertheless, there are some potential problems such as intelligent release efficiency, subsequently, influence cell toxicity and blood circulation stability. A novel type of stimuli-responsive nanoparticle was developed in accordance with the specific tumor microenvironment to deliver gambogic acid (GA). Herein, we successfully connected GA with mPEG via two different sensitive linkages, valine-citrulline (VC) and cystamine. The structure was characterized by ESI-MS, 1 H NMR, FT-IR or MALDI-TOF-MS. The mPEG-VC-SS-GA-NPs (PVSG-NPs) were rapidly prepared. The properties of nanoparticles, including solubility, particle size, morphology, and sensitive drug release performance, were investigated. Compared to single sensitive conjugate (mPEG-SS-GA-NPs, PSG-NPs), PVSG-NPs demonstrated greater solubility and higher sensitive release profile. Cytotoxicity test indicated that PVSG-NPs had apparent cytotoxicity on HepG2 cells and reduced cytotoxicity on normal cells. Additionally, PVSG-NPs mainly kill HepG2 cells by inducing early and late apoptosis and restraining the G0/G1 phase proliferation. Albumin adsorption test revealed that the PVSG-NPs had little albumin combination, consequently, enhancing their circulation constancy. In summary, our findings suggested the novel PVSG-NPs capable of being used for tumor targeting and further practical applications.